The Abundance of Pioneer Vegetation and Their Interaction with Endomycorrhiza at Different Land Qualities after Merapi Eruption - Cahyono Agus; Dewi Wulandari (Institut Pertanian Bogor (IPB University), 2012)
Eruption of Merapi volcano caused accumulation of lahar materials that led to extensive land degradation. This research was to study the population of pioneer plants and their correlation with endomycorrhiza population at different land qualities after Merapi eruption. Samples of soil, pioneer plants, and endomycorrhiza were collected from Merapi volcano, 1 year after eruption, using stratified sampling method based on plant densities, with the following categories: dense vegetation, moderately dense vegetation, sparse vegetation, and control (bare land), with 3 replications for each category. Pioneer plants and endomycorrhiza were identified. Plant biomass, soil pH, total-C,-N, and exchangeable-K, -Ca, -Mg, -Fe were analyzed. The abundance of pioneer plants and their interaction with mycorrhiza was strongly correlated with depth of eruption material, quantity of sandy texture, soil pH, total-C and total-N, exchangeable-K, exchangeable-Ca, exchangeable-Mg, and exchangeable-Fe. Among the 12 identified pioneer plants, only Acacia villosa, Fiurena ciliaris, and Bidens pilosa were recommended as plant-remediator to improve soil chemical, physical and biological properties. Among the 3 genera of endomycorrhiza (Acaulospora, Gigaspora, Glomus), only Acaulospora was recommended to be a biological agent to rehabilitate sandy soil area. This research indicated that adaptive pioneer plants and endomycorrhiza were likely to be suitable for biological agents to stimulate recovery of degraded land through improvement of physical, chemical, and biological properties, that will stimulate plant growth and biodiversity.